Experimental of Wood Gasification in Suction Biomass Gasifier - Ahmad, Muhammad Iqbal; Alauddin, Zainal Alimuddin Zainal; Soid, Shahril Nizam Mohamed; Mohamed, Mazlan; Yusoff, Mohd Huzaifah (Trans Tech Publications, 2012)
Biomass is one of the alternatives energy which are abundant, relatively cheap, and widespread availability. This paper is aim to show the process finding according experimental work of wood using suction biomass gasifier. Energy can be extracted from biomass through gasification process. The experiment focuses on woody gasification. A suction biomass gasifier has been built and operated under stable condition which fueled from wood waste and air as gasifying agent. The biomass feeding rate was varied from 3 to 5.5kg/hr. Result show that producer gas contains CO in 20-30% in volume and H2 found to be varying between 14 and16% vol. The low heating value (LHV) from this woody gasification around 4 -5 MJ/Nm3. Carbon conversion efficiency also measured as a parameter to indicate biomass-gas conversion.